PENGARUH PENDIDIKAN DAN PELATIHAN, KEPEMIMPINAN, TANGGUNG JAWAB DAN KOMPENSASI TERHADAP KINERJA GURU - Saiful Hunta; Meioon Ibrahim; Mohamad Afan Suyanto (STKIP PGRI Situbondo, 2022)
This study aims to determine and analyze the variables of education and training (training), leadership, responsibility and compensation affect the performance of State Junior High School teachers in Marisa District. The population that is used as the research target is the parties related to the performance of State Junior High School Teachers, a total of 70 people, and all of them are respondents using multiple linear regression analysis models. Based on the results of statistical analysis through the SPSS Program, it shows that together the four independent variables, namely: the influence of education and training, leadership, responsibility, and compensation have a positive and significant influence on teacher performance and leadership has a dominant significant influence on teacher performance. State Junior High School in Marisa . District